Monstrous Women in Comics, Samantha Langsdale and Elizabeth Rae Coody (eds) 2020. Issue 2 (1st November 2020) - Austin, Hailey J.
Review of: Monstrous Women in Comics, Samantha Langsdale and Elizabeth Rae Coody (eds) (2020)Jackson, MS: University Press of Mississippi, 295 pp., 35 b&w illustrationsISBN 978-1-49682-763-0, p/bk, $30